Fairies, feminists & queer anarchists: geographies of squatting in Brixton, south London - Bettocchi, Milo (2021)
This thesis assembles cultural, historical, political, affective and infrastructural geographies of squatting in Brixton, south London. It does so to spatialise the complex material and affective processes through which identities, collectivities and political projects are assembled, negotiated and navigated; to document vital spaces, histories, dynamics, political lineages and struggles which the literature on squatting in England has overlooked; and to critically interrogate and expand how squatting in England has been conceptualised. In pursuing these aims, this thesis insists on and demonstrates the co-constitution of the spatial and the political. Where work on squatting in England has largely concentrated on a narrow range of collectives, spaces and time periods and has neglected how squatting has intersected with anti-racist, decolonial, feminist and LGBTQ struggles and politics, this thesis responds to these gaps. Chapters focus on what became known in the 1970s as the Brixton Gay Community, an experiment in communal living and revolutionary politics by gay men; on the Brixton Black Women’s Group, a socialist, anti-imperialist feminist organisation active in the 1970s and 1980s; on Queeruption, an anarchist queer festival organised out of a squat in the late 1990s; and on the House of Brag, a queer squatting collective active between 2012 and 2014. I argue that thinking squatting through these can profoundly reframe our understandings of squatting. To this end, I have drawn on 24 original interviews as well as on a broad range of archival material. In making important contributions to critical considerations of squatting in England, this thesis draws on and extends a variety of bodies of literature, including geographies of urban sexualities, queer geographies, anarchist geographies, geographies of affect and emotions, as well as geographies of feminist organising in England and social movements more broadly.